No Panorama Judges for Saturday Yet - Ali, Nazim (Daily Express)
The big Panorama show has run into another snag as organisers were unable to come up with a panel of judges. The date itself is posing a problem to finding a panel of judges.
Keywords: Steel bands (Music) -- Competitions -- Judging; Steel band music -- Trinidad and Tobago; Pan Trinbago (Organization); Steel bands (Music) -- Trinidad and Tobago